2017
DOI: 10.18203/2349-3933.ijam20171476
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and comparison of 3 mortality prediction models SAPS II, APACHE II and SOFA for prediction of mortality in patients of sepsis

Abstract: Background: Little is known about outcomes of patients admitted to the ICU with severe sepsis and septic shock, despite the seriousness of sepsis as a public health problem in developing countries. Understanding sepsis outcome studies is hampered by lack of an agreed severity of illness scoring system for sepsis patients. The objective of the present study is to assess and compare the validity of 3 mortality prediction models SAPS 2, APACHE II and SOFA for prediction of mortality in patients of sepsis.Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
2
4
0
1
Order By: Relevance
“…In these studies and some other previous reports [11,13], the SOFA score system had the lowest discriminatory power between survived and deceased patients as compared with the three other scoring systems. This result can be attributed to the design of the SOFA scoring system.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…In these studies and some other previous reports [11,13], the SOFA score system had the lowest discriminatory power between survived and deceased patients as compared with the three other scoring systems. This result can be attributed to the design of the SOFA scoring system.…”
Section: Discussionsupporting
confidence: 58%
“…They had calculated the AUROC to be 0.78 for APACHE II, which are similar to our findings. In contrast to these studies, several studies reported that the SAPS II score was superior to the APACHE II score for mortality prediction [13,18]. Regardless of either APACHE II or SAPS II is better, many studies reported no statistically significant difference between APACHE II and SAPS II, and even a good correlation between them [8,12,[19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it suggests that the potential mechanisms of the protective effect could also be related to the use of medication that led to a well control of symptoms of asthma. Apart from the confounding factors considered in Zein et al’s study 28 , the illness severity score SAPS II was also adjusted in our study, which would greatly increase the strength of our study, since it has been reported to be associated with prognosis of sepsis patients 38 and therefore relieve the concern about potential confounding bias.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity and specificity of both scoring systems in our study were not very satisfactory (SAPS II: 100% sensitivity and 41.67% specificity and APACHE IV: 50% sensitivity and 87.5% specificity) when compared with others. Sharma S et al [23] found SAPS II predicting with 88.23% sensitivity and 100% specificity in sepsis patients. In a Turkish intensive care unit, Ayazoglu T, [21] observed excellent result by APACHE IV on stroke patients (at score >84.5, 94.7% sensitivity and 94.4% specificity).…”
Section: Variablesmentioning
confidence: 96%